2008
DOI: 10.1007/s00330-008-1090-y
|View full text |Cite
|
Sign up to set email alerts
|

Training on a vascular interventional simulator: an observational study

Abstract: Radiology registrars were observed performing a left renal artery angioplasty using a proprietary training simulator up to five times during their first year of training. Total procedure time, fluoroscopy times, and metric information from the machine were recorded. Each step of the procedure was judged by an observer and a mistake profile was generated. Fifty-two runs were completed by 12 trainees. The mean procedure time decreased from 16.6 min to 9.8 min over the five runs. The number of mistakes ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Second, previous studies exceeded ours in the extent to which the technical skills of participants were tested (examination of multiple simulations over time or of several tasks contemporaneously and complexity of task) and evaluated (utilization of both subjective observational assessments and multiple objective metrics such as also fluoroscopy time and contrast media usage). 19 These studies reported statistically significant differences in endovascular skill relative to level of clinical or simulated experience, 20-25 and positive correlations between VG play and laparoscopic or endovascular surgical skill. 5-8 Furthermore, our sample size was below average compared to the previous literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, previous studies exceeded ours in the extent to which the technical skills of participants were tested (examination of multiple simulations over time or of several tasks contemporaneously and complexity of task) and evaluated (utilization of both subjective observational assessments and multiple objective metrics such as also fluoroscopy time and contrast media usage). 19 These studies reported statistically significant differences in endovascular skill relative to level of clinical or simulated experience, 20-25 and positive correlations between VG play and laparoscopic or endovascular surgical skill. 5-8 Furthermore, our sample size was below average compared to the previous literature.…”
Section: Discussionmentioning
confidence: 98%
“…First, IR skill was evaluated on the previously validated VIST G5® Simulator (Mentice AB, Gothenburg, Sweden) ( Figure 1). [19][20][21][22][23][24][25] The VIST G5® is a high-fidelity endovascular simulator which supports real clinical devices, table controls, and advanced haptic feedback. Tools are inserted into a control box to interact with a number of different computer software-generated clinical scenarios.…”
Section: Part 1: Ir Skillmentioning
confidence: 99%
“…ST can be particularly helpful to teach the basic skills rapidly, such as arterial puncture and selective catheterisation, allowing the trainee to concentrate on the more advanced aspects of the procedure. It reduces the burden on trainers, 74,75 and increases patient safety. ST can also be valuable for experienced operators to maintain and update their skills, with objective feedback.…”
Section: Improving Procedures Performance Learning Curve and Procedurementioning
confidence: 99%
“…The main benefit is that trainees reduce the learning curve for new procedures. 29,30 Using simulators, trainees can learn the basic catheter skills outside the cath lab, which allows them to focus their attention on the more advanced aspects of the procedure in a real case. This would overall reduce the number of procedures required to achieve proficiency.…”
Section: Benefits Of Simulation Trainingmentioning
confidence: 99%